Progressive chronic SARS‐CoV‐2‐positive giant cell myoendocarditis with atrial standstill and sudden cardiac death. (29th July 2021) - Blagova, Olga; Ainetdinova, Dilyara; Sedov, Alexey; Lutokhina, Yulia; Kogan, Evgeniya; Kukleva, Anna; Sedov, Vsevolod; Zaitsev, Alexander; Vasukov, Sergey; Alexandrova, Svetlana; Sarkisova, Natalya
Abstract: Giant cell myocarditis (GCM) is a rare condition. Its association with SARS‐CoV‐2 has not been described before. The 46‐year‐old female patient was admitted to the clinic on September 2020. She had 7 year adrenal insufficiency history and infarct‐like debut of myocardial disease in November 2019. After COVID‐19 in April 2020, cardiac disease progressed. The examination showed low QRS voltage, QS complexes in V1 –V5 leads, atrial standstill, left ventricular systolic and restrictive dysfunction, elevated anti‐heart antibodies, and subepicardial late gadolinium enhancement by magnetic resonance imaging. Endomyocardial biopsy and pacemaker implantation were performed, but the patient died suddenly due to ventricular tachycardia or ventricular fibrillation (the resuscitation was ineffective). The autopsy revealed GCM, SARS‐CoV‐2, and Parvovirus B19 were detected in the myocardium. The role of SARS‐CoV‐2 in the pathogenesis of autoimmune myocarditis is discussed.